Investigation of the antimicrobial activity of some species belonging to pinaceae family - Emhemed, Hend M. E. (Kastamonu Üniversitesi, 2017)
This study aims to reveal the antimicrobial effect of the essential oil obtained by steam distillation method from some Pinaceaea species on pathogenic fungi and bacteria. In this study oil was extracted from Pinus nigra subsp. pallasiana, Abies normanniana subsp. equi-trojani, Pinus sylvestris, Picea orientalis, Pinus brutia and Cedrus libani then tested against Gram-positive bacteria: Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecium, Enterococcus faecalis, Klebsiella pneumoniae and Bacillus subtilis. Gram-negative bacteria: Salmonella typhimurium, Salmonella kentucky, Salmonella infantis, Salmonella enteritidis, Escherichia coli, Enterobacter aerogenes, Pseudomonas aeruginosa and Pseudomonas fluorescens, and fungi; Candida albicans.
Pinaceae familyasina ait bazi taksonlarin antimikrobiyal aktivitesinin incelenmesi
Keywords: Pinus nigra subsp. pallasiana, Abies normanniana subsp. equi-trojani, Pinus sylvestris, Picea orientalis, Pinus brutia, Cedrus libani, Antimicrobial, Essential oil, GC-MS analysis